2014
DOI: 10.1109/jlt.2014.2312321
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Optical Modulators in Optimized Nonlinear Compensated LTE RoF System

Abstract: This document may differ from the final, published version of the research and has been made available online in accordance with publisher policies. To read and/or cite from the published version of the research, please visit the publisher's website (a subscription may be required.)IEEE/OSA Journal of Lightwave Technology 1  Abstract-In this paper, we investigate a nonlinear compensation technique with two different architectures using direct modulation (DM) and external modulation (EM) techniques, termed as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…Investigated Direct Modulation (DM) and External Modulation (EM), and direct modulator on QAM (Quadrature Amplitude Modulation) has exhibits to mitigate SBS (stimulated Brillouin scattering) and optimization nonlinear compensated for LTE (Long Term Evolution)-RoF with varied launch power for enhanced power budget [3]. Another line of research is aimed to demonstrate of the nonlinear compensation LTE-RoF based on DMFD (Direct Modulation Frequency Dithering) and EMFD (External Modulation Frequency Dithering) also to mitigate SBS including analysis of QPSK (Quadrature Phase Sift Keying), 16 QAM, and 64 QAM scheme [4]. On the other hand, was investigated to optimized launch power for the [5].…”
Section: Introductionmentioning
confidence: 99%
“…Investigated Direct Modulation (DM) and External Modulation (EM), and direct modulator on QAM (Quadrature Amplitude Modulation) has exhibits to mitigate SBS (stimulated Brillouin scattering) and optimization nonlinear compensated for LTE (Long Term Evolution)-RoF with varied launch power for enhanced power budget [3]. Another line of research is aimed to demonstrate of the nonlinear compensation LTE-RoF based on DMFD (Direct Modulation Frequency Dithering) and EMFD (External Modulation Frequency Dithering) also to mitigate SBS including analysis of QPSK (Quadrature Phase Sift Keying), 16 QAM, and 64 QAM scheme [4]. On the other hand, was investigated to optimized launch power for the [5].…”
Section: Introductionmentioning
confidence: 99%
“…Compensated nonlinear on RoF also observes in another paper to achieve high power budget using power gain. The other project proposes to investigate performance and characteristic OFDM based on modulation for Rolf [1], [3], [4]. A modeling system to achieve high performance based on OFDM optical network and introduce a novel ICI (Inter Carrier Interference) reduction algorithms cancellation under the various channel environments has already been considered in the literature [5], [6].…”
mentioning
confidence: 99%
“…The principle of operation is based on simple amplifying and forwarding RNs with RoF acting as the interface between the eNB and RN [4][5][6][7][8]. In other words, instead of eNB, the RN delivers the LTE signal to the UE at the cell edge.…”
mentioning
confidence: 99%
“…As a solution, we recently proposed a direct modulation based frequency dithering (DMFD) method for nonlinear compensation specifically designed for the LTE RoF system [5], which enabled the use of higher optical launch powers. Further optimizations of this method were carried out in the perspective of optical modulators [6] and dithering frequency f d with higher order modulations [7]. In [6], it is shown that DMFD method introduces an additional ~3 dB optical power penalty in comparison to external modulation while imposing a lower cost.…”
mentioning
confidence: 99%
See 1 more Smart Citation